Exploring molecular evolution of Rubisco in C3 and CAM Orchidaceae and Bromeliaceae - Hermida-Carrera, Carmen; Fares, Mario A.; Font-Carrascosa, Marcel; Kapralov, Maxim V.; Koch, Marcus; Mir, Arnau; Molins, Arántzazu; Ribas-Carbó, Miquel; Rocha, Jairo; Galmés, Jeroni (BMC evolutionary biology, 2020)
The CO2-concentrating mechanism associated to Crassulacean acid metabolism (CAM) alters the catalytic context for Rubisco by increasing CO2 availability and provides an advantage in particular ecological conditions. We hypothesized about the existence of molecular changes linked to these particular adaptations in CAM Rubisco. We investigated molecular evolution of the Rubisco large (L-) subunit in 78 orchids and 144 bromeliads with C3 and CAM photosynthetic pathways. The sequence analyses were complemented with measurements of Rubisco kinetics in some species with contrasting photosynthetic mechanism and differing in the L-subunit sequence.
Die 3 in C3 ist tiefgestellt
Gesehen am 30.03.2020